1983
DOI: 10.1145/357980.357993
|View full text |Cite
|
Sign up to set email alerts
|

Programming semantics for multiprogrammed computations

Abstract: The semantics are defined for a number of meta-instructions which perform operations essential to the writing of programs in multiprogrammed computer systems. These meta-instructions relate to parallel processing, protection of separate computations, program debugging, and the sharing among users of memory segments and other computing objects, the names of which are hierarchically structured. The language sophistication contemplated is midway between an assembly language and an advanced algebraic language.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
145
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(146 citation statements)
references
References 10 publications
0
145
0
1
Order By: Relevance
“…From studying capabilities [DH65] in general, and especially from the clarifications about capability based security recently provided by Miller and Shapiro [MS03], we concluded that modeling collaborative behavior is crucial when modeling capabilities accurately. When propagating authority from one subject to another, the authority reducing behavior of the subjects involved should be taken into account.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…From studying capabilities [DH65] in general, and especially from the clarifications about capability based security recently provided by Miller and Shapiro [MS03], we concluded that modeling collaborative behavior is crucial when modeling capabilities accurately. When propagating authority from one subject to another, the authority reducing behavior of the subjects involved should be taken into account.…”
Section: Introductionmentioning
confidence: 92%
“…The security concept we call a capability was introduced by Dennis and Van Horn [DH65] in the 1965. The concept is very simple: make designation unforgeable and combine it with authority, then you have a capability.…”
Section: Capability Security and Capability Secure Languagesmentioning
confidence: 99%
“…For components which a r e programs, t h i s problem i s o f t e n solved by d e f i n i n g s p e c i a l hardware i n s t r u c t i o n s and assuming t h e e x c l u s i v e e x e c u t i o n of t h e s e i n s t r u c t i o n s L 7,9,10,15,16 1. I n I 4 1 a model f o r p a r a l l e l computer systems w a s proposed i n which fundamental-mode flow t a b l e s are used t o d e s c r i b e t h e o p e r a t i o n of each component.…”
Section: Has Solved a S L I G H T L Y D I F F E R E N T V E R S I O Nmentioning
confidence: 99%
“…It started as a way to protect "primitive" resources such as memory segments [7], but was soon generalized [43] into a protected ability to invoke arbitrary services provided by other processes. For each process, there is a table associating small numbers (similar in spirit to Unix file descriptors) with the capabilities held by that process.…”
Section: Capability Operating Systemsmentioning
confidence: 99%